Smart Detergent Vending Machine with Real-time Quantity Check using IoT - Abdullah Mohammed Basalam, Ir. Ilanur Muhaini Mohd Noor (International Journal of Advanced Science and Technology, 2020)
Vending machine represent an automatic seller machine, where  about  buyer  enough  enter  a payment in terms of coin or banknote to  get  the  product  wanted  which  is  there  are  in  the  vending  machine. This project investigates several vending machines and identifies that the current detergent dispensing vending machine costly with some limitation in features such as IoT. Thus, this project put forward to propose a low cost and  user friendly detergent dispensing vending machine with IoT support to monitor product level in real-time and remotely. In this project, a prototype is developed using aluminum, plywood and acrylic for the mechanical structure, where Arduino Mega2560 is utilized as the main controller with 480x320 touch screen LCD. In addition, the prototype includes a coin acceptor which is program to accept only 50 cent as payment per product, and RFID card for smart payment option. The prototype is design to dispense three different detergent, soap, bleach and softener. The experimental results show that the system performance is good with average coin recognition accuracy up to 99%, Card payment accuracy up to 99% and dispensing accuracy up to 89%. In addition, the real-time quantity monitoring performance is measured in terms of accuracy and reliability is up to 100%. In conclusion, the proposed design shows good performance as well as low power consumption compared to conventional vending machine of similar features. This electronic document is a “live” template and already defines the components of your paper [title, text, heads, etc.] in its style sheet.